A inserção dos psicólogos no Sistema Único de Assistência Social : identidade, práticas e desafios - Nadal, Ana Hertzog Ramos de (2016)
This Master thesis is composed of two empirical articles and aims to analyze the psychological practices from the speech directly involved workers in the practical field of the National Social Assistance Policy. The first one aims to understand the discourses that produce psychological practices in the field of social assistance, trying to understand how it is perceived interdisciplinary work by psychologists inserted in this field, and to investigate how to build the psychological practices collectively and as a professional category. A focal group of psychologists and one social worker of Porto Alegre and its metropolitan area have participated. It was done an analysis of thematic content. The analysis created seven categories grouped in the axes “Psychological Practices, Work and Policy of Assistance”. In the discourse of those workers, it is highlighted the fatalism, the exploitation and the impotence that is reproduced in the talk and in the feeling of the professionals and that is also fruit of a context of injustice and oppression, lived by the own workers. In the second study, it was aimed to, besides the psychological practices in the SUAS, understand how the psychologists of assistance build and reaffirm its professional identity. Psychologists that work in CRAS of Porto Alegre participated in this study and they were interviewed individually, furthermore, the transcriptions of the focal groups of the first study were also analysed. It was done an analysis of the thematic content and five categories were listed from the literature: identity as negotiated experience of the self, affiliation, trajectory of the apprenticeship, multi-affiliation and globally defined affiliation, but experienced locally. On the analysis it is highlighted the difficulty of professionals to perceive itself worker of assistance, besides to position itself collectively and politically. It was concluded, through those two studies, that, for the psychologist worker of assistance, it is necessary to assume political position in service of social transformation; articulate itself as a professional category and also perceive and identify itself as a worker of the assistance. However, this is yet a professional category that is identified with the traditional clinical practice, even that some transforming practices are already being produced.